2019
DOI: 10.1002/cam4.2578
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participation and detection rate of upper gastrointestinal cancer from population‐based screening program in China

Abstract: Upper gastrointestinal cancer (UGC) screening has been widely implemented in many Asian countries. However, there is little evidence of participation and diagnostic yields in population‐based UGC screening in China. The participation rate and detection of upper gastrointestinal lesions in this program were reported and related factors were explored. The analysis was conducted in the context of the Cancer Screening Program in Urban China, which recruited 179 002 eligible participants aged 40‐74 years from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
2
26
2
Order By: Relevance
“…The study methods are described elsewhere. 5 In brief, residents aged 40 to 74 years living in the selected communities of the 8 participating cities were approached by trained staff by means of telephone calls and personal encounter. Social media and community advertisement were used to raise the public awareness of this cancer screening program.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methods are described elsewhere. 5 In brief, residents aged 40 to 74 years living in the selected communities of the 8 participating cities were approached by trained staff by means of telephone calls and personal encounter. Social media and community advertisement were used to raise the public awareness of this cancer screening program.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…In October 2012, the National Health Committee of China announced the launch of the Cancer Screening Program in Urban China (CanSPUC), which targets 6 types of cancer that are most prevalent in urban areas, including lung cancer, female breast cancer, esophageal cancer, gastric cancer, colorectal cancer, and liver cancer. 5 Eligible participants are recruited in the communities of the study regions and are invited to undergo cancer screening free of charge. Participants are first invited to take a cancer risk assessment using an established clinical cancer risk score system, and those who are evaluated to be at high risk for specific types of cancer are recommended to take the appropriate screening intervention per the study protocol.…”
Section: Introductionmentioning
confidence: 99%
“…CanSPUC is an ongoing national cancer screening program launched in October 2013 in Henan province of China. Study methods have been described elsewhere (10). In short, social media and community advertising were used to raise public awareness about the cancer screening process.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Since October 2012, the Chinese government has launched a population-based Cancer Screening Program in Urban China (CanSPUC). Except for CRC, lung cancer, female breast cancer, liver cancer, esophageal cancer, and gastric cancer were all targeted (10). Henan started this program in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the bene ts of cancer screening, the targeted population must participate in it as much as possible, which places high demands on population adherence. However, the participation rate of the targeted population in the UGC screening programme in Henan province, China, has been reported to be only 18.4% [14]. A project summary of UGC screening reported that the quality of screening services in China was not optimistic, characterized by low early diagnosis rates, low 5-year survival rates, weak service levels and poor population adherence, especially in rural areas [15].…”
Section: Introductionmentioning
confidence: 99%